Intra-Regional Variation in Industrial Development in Mau District, Uttar Pradesh - Ahmad, Mumtaj; Alam, Mahtab (National Geographical Journal of India, 2022)
Industrialization plays a crucial role in the economic development of a region but many regions face the regional disparity in the development of industry mainly due to natural as well as historical process of development. In the present paper, an attempt has made to analyze the intra-regional disparity in Mau district. Mau district has suffered from intraregional disparity and inequality. Some blocks of this district are very advanced in the development of textile industry and some blocks are very backward in textile industries due to inefficiency of different facilities like infrastructure, government policies and their planning. The present work is entirely based on secondary sources of data which is collected from Sankhyaki Patrika (Govt. of Uttar Pradesh). This paper tries to point out the causes of intraregional disparity of the regions and also explain the consequences of intra-regional variations in industrial development. In the present work simple percentage method has been used for the analysis of data to demarcate the regional disparity. Policy measures have also been suggested to reduce the intra-regional disparity and to achieve the overall growth and development of industries in the regions.